Unmanned Aerial Vehicle (UAV) : real time control system - Peng, Xi (2016)
The Unmanned Aerial Vehicle (UAV) is an emerging technology being adapted for use in military, commercial and civil areas and it is brought into sharp focus among many countries. The UAV is a pilotless airplane that can be controlled by radio signal remote or fly autonomously based on flight path programmed or more complicated autonomous systems. UAV are designated to carry many sensors in order to perform various missions such as GPS, compass, laser scanner and digital camera. With those sensors, the UAV can be used in a wide range of applications such as surveillance, remote sensing, logistics and rescue etc. This project’s objective is to design and develop a UAV real-time control system which meets the surgent requirements on UAV capabilities and allows the user to efficiently and conveniently manoeuvre the UAV. Mobile device playing as UAV controller was explored and Raspberry Pi Model 3 and Android system was selected for this project. This project demonstrated the advantages and disadvantages of mobile device control mechanism.